AYURVEDIC MANAGEMENT OF ALOPECIA AREATA USING VIDDHAKARMA AS A PARA-SURGICAL PROCEDURE: A CASE STUDY - Dr. Vishal M. Vasaiya; Prof. (Dr.) Chandrakant Pawar; Prof. (Dr.) Shailesh Jaiswal (The Bioscan, 2026)
Alopecia areata is a common autoimmune dermatological disorder characterized by non-scarring, patchy hair loss. In Ayurveda, this condition is described as Indralupta and is attributed to Tridoshaja involvement with Rakta Dushti and obstruction of hair follicles (Romakupa Avarodha). Conventional management includes corticosteroids and immunomodulators, which may provide temporary relief but are often associated with adverse effects and recurrence. The present case report evaluates the effectiveness of Viddhakarma, a para-surgical procedure described in Ayurvedic texts, along with internal medications in the management of Indralupta. A 21-year-old male presented with patchy hair loss over the scalp for one year. Viddhakarma was performed twice weekly for six weeks, supported by Panchatikta Ghrita and Asthiposhaka Vati. Significant hair regrowth was observed, with marked improvement in SALT score and no adverse effects. This case highlights the potential role of Viddhakarma as a safe, cost-effective, OPD-based Ayurvedic intervention for alopecia areata.